Atypical C-ANCA following high dose intravenous immunoglobulin. Issue 3 (1st March 1999) - Jolles, S; Deacock, S; Turnbull, W; Silvestrini, R; Bunn, C; White, P; Ward, M
Abstract : AIMS: (1) To assess a range of intravenous immunoglobulin products for atypical classical antineutrophil cytoplasmic antibody (C-ANCA) staining and to determine if this is present in patients treated with high dose intravenous immunoglobulin (2 g/kg/month) and replacement doses (200 mg/kg fortnightly); (2) using the United Kingdom national external quality assessment scheme (NEQAS), to determine if laboratories could differentiate this pattern from classical ANCA. METHODS: ANCA testing was performed on 30 batches of intravenous immunoglobulin from several manufacturers. Six patients treated with high dose intravenous immunoglobulin and 11 receiving replacement doses of immunoglobulin for hypogammaglobulinaemia were tested for ANCA by indirect immunofluorescence on cytospin preparations of ethanol fixed neutrophils and by enzyme linked immunosorbent assay (ELISA). One of the positive immunoglobulin batches was tested blindly by 125 laboratories involved in NEQAS by indirect immunofluorescence and by ELISA in some laboratories. RESULTS: 16 of 31 batches of intravenous immunoglobulin from six different manufacturers were atypical C-ANCA positive. Three of six patients receiving high dose intravenous immunoglobulin and none of 11 patients on replacement doses were atypical C-ANCA positive. The results of the NEQAS assessment by indirect immunofluorescence were 68% C-ANCA positive, 17% negative, 9% atypical C-ANCA, and 6% P-ANCA. CONCLUSIONS: Some but not all intravenous immunoglobulin products yield a positive atypical cANCA by indirect immunofluorescence. An identical pattern may be observed in patients receiving high dose intravenous immunoglobulin but not in those on replacement doses. Of laboratories participating in NEQAS, 68% reported this pattern as cANCA. This reinforces the importance of reporting only "classical ANCA, " defined by international ANCA workshops, to maintain the specificity of ANCA immunofluorescence and its close disease associations.